2003
DOI: 10.1007/s00221-003-1432-6
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity of the goldfish optic tectum with the mesencephalic and rhombencephalic reticular formation

Abstract: The optic tectum of goldfish, as in other vertebrates, plays a major role in the generation of orienting movements, including eye saccades. To perform these movements, the optic tectum sends a motor command through the mesencephalic and rhombencephalic reticular formation, to the extraocular motoneurons. Furthermore, the tectal command is adjusted by a feedback signal arising from the reticular targets. Since the features of the motor command change with respect to the tectal site, the present work was devoted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 71 publications
2
21
0
Order By: Relevance
“…It is possible that this cell label reflects leakage of tracer from dap fibers into collaterals of abducens cells. On the other hand, cell body and terminal label in and around the abducens nucleus following injections of dextran amine into the OT have been observed in adult goldfish [Pérez-Pérez et al, 2003]. The absence of direct tectal efferents to the abducens nucleus in our data is consistent with previous results in adult R. temporaria [Cochran et al, 1984].…”
Section: Species and Developmental Variability In Tectal Brainstem Prsupporting
confidence: 83%
“…It is possible that this cell label reflects leakage of tracer from dap fibers into collaterals of abducens cells. On the other hand, cell body and terminal label in and around the abducens nucleus following injections of dextran amine into the OT have been observed in adult goldfish [Pérez-Pérez et al, 2003]. The absence of direct tectal efferents to the abducens nucleus in our data is consistent with previous results in adult R. temporaria [Cochran et al, 1984].…”
Section: Species and Developmental Variability In Tectal Brainstem Prsupporting
confidence: 83%
“…MeLr and MeLc extend elaborate dendrites into the deeper layers of the tectum. Here, the cell bodies of tectofugal projection neurons are situated (Meek and Schellart, 1978;Nguyen et al, 1999), which, in other teleosts, have been reported to send a predominantly ipsilateral and excitatory projection to the nMLF (Bosch and Paul, 1993;Herrero et al, 1998a;Niida et al, 1998;Zompa and Dubuc 1998a,b;Isa and Sasaki, 2002;Torres et al, 2002;Perez-Perez et al, 2003). MeLr and MeLc extend axons into the spinal cord, arborizing predominantly in its rostral segments, in which their axon terminals colocalize with motor neurons and interneurons .…”
Section: Discussionmentioning
confidence: 78%
“…However, additional study is necessary to correlate the neuroanatomically identified projection patterns with the electrophysiologically characterized motor command map in the tectum. In goldfish, the injection sites of tracers in the tectum show a colinear anterior-posterior relationship with the sites containing the peak number of labeled synaptic boutons in the mesencephalic reticular formation, although such a relationship is not found in the rhombencephalic reticular formation (Perez-Perez et al, 2003). The discrepancy between these observations in goldfish and our results is likely attributable to the differences in labeling strategies (single-neuron labeling vs tracer injection) and in examined parameters for the tectum and the hindbrain (somatic locations and the final projection site vs injection sites and the number of synaptic boutons).…”
Section: Genetic Single-neuron Labeling In Zebrafishmentioning
confidence: 99%